Carbon isotope systematics of Turrialba volcano, Costa Rica, using a portable cavity ring‐down spectrometer. (27th July 2017) - Malowany, K. S.; Stix, J.; de Moor, J. M.; Chu, K.; Lacrampe‐Couloume, G.; Sherwood Lollar, B.
Abstract: Over the past two decades, activity at Turrialba volcano, Costa Rica, has shifted from hydrothermal to increasingly magmatic in character, with enhanced degassing and eruption potential. We have conducted a survey of the δ 13 C signatures of gases at Turrialba using a portable field‐based CRDS with comparison to standard IRMS techniques. Our δ 13 C results of the volcanic plume, high‐temperature vents, and soil gases reveal isotopic heterogeneity in the CO2 gas composition at Turrialba prior to its recent phase of eruptive activity. The isotopic value of the regional fault system, Falla Ariete (–3.4 ± 0.1‰), is in distinct contrast with the Central crater gases (–3.9 ± 0.1‰) and the 2012 high‐temperature vent (–4.4 ± 0.2‰), an indication that spatial variability in δ 13 C may be linked to hydrothermal transport of volcanic gases, heterogeneities in the source composition, or magmatic degassing. Isotopic values of CO2 samples collected in the plume vary from δ 13 C of −5.2 to −10.0‰, indicative of mixing between atmospheric CO2 (–9.2 ± 0.1‰), and a volcanic source. We compare the Keeling method to a traditional mixing model (hyperbolic mixing curve) to estimate the volcanic source composition at Turrialba from the plume measurements. The predicted source compositions from the Keeling and hyperbolic methods (–3.0 ± 0.5‰ and −3.9 ± 0.4‰, respectively) illustrate two potential interpretations of the volcanic source at Turrialba. As of the 29 October 2014, Turrialba has entered a new eruptive period, and continued monitoring of the summit gases for δ 13 C should be conducted to better understand the dominant processes controlling δ 13 C fractionation at Turrialba. Key Points: Spatial heterogeneity in the δ 13 C of volcanic gases imply hydrothermal modification of volcanic CO2 at Turrialba The hyperbolic mixing model for predicting volcanic end‐member compositions is preferred to the Keeling method Diurnal changes in δ 13 C can impact volcanic plume measurements in densely vegetated areas